Fisheries Stakeholder Perspective Quantification on Freshwater Fish Cultivation Diversification - Arsanti Arsanti; Rodhi Firmansyah; Ramona Indah Bagariang; Ipan Adityamada; Rizky Ondolan Pulungan (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
There is still a different perspective on the fishery aspect of the importance of diversifying the fish farming business in freshwater, causing a low quantity of aquaculture entrepreneurs as well as the diversity of fish cultivation businesses in freshwater. Therefore, a reference basis is needed through a study on the perspective of these stakeholders to determine an appropriate cultivation business strategy to be implemented. The study used interview methods and questionnaires for 40 stakeholder respondents in the field of fisheries and analyzed with Analysis Hierarchy Process (AHP). The results show that land suitability, supportive laws and regulations, market demand, public perception/perspective, and adequate availability of human resources are the main contributing factors in the expansion of the freshwater fish farming business on Sibundong river. The actors expected by the community in the expansion of fish aquaculture business are Bappeda, Freshwater Seed Hall, Marine and Fisheries Affairs and Government of Central Tapanuli, and Matauli College of Fisheries and Marine Science. All of them can be achieved by coordinating between relevant agencies intensively, conducting training/making pilot pools of freshwater cultivation, improving the distribution channels of freshwater aquaculture fisheries, conducting multi-species cultivation, and conducting environmentally-minded cultivation.